Evaluation and comparision of dc resistivity of NiZrxCoxFe2−2xO4, Ni0.5Sn0.5CoxMnxFe2−2xO4, Mg1−xCaxNiyFe2−yO4 and Mg1−xNixCoyFe2−yO4 nanocrytalline materials. (2nd November 2017) - Ali, Rajjab; Gilani, Zaheer Abbas; Shifa, Muhammad Shahzad; Asghar, H M Noor Ul Huda Khan; Khan, Muhammad Azhar; Anjum, Muhammad Naeem; Usmani, Muhammad Nauman; Warsi, Muhammad Farooq; Khawaja, Imtiaz U
Abstract: Four series nanocrystalline ferrites with nominal composition, NiZr x Co x Fe2−2 x O4 ( x = 0.0, 0.2, 0.4, 0.6, 0.8) Ni0.5 Sn0.5 Co x Mn x Fe2−2 x O4 ( x = 0.0, 0.2, 0.4, 0.6, 0.8), Mg1− x Ca x Ni y Fe2− y O4 ( x = 0.0, 0.2, 0.4, 0.6, 0.8; y = 0, 04, 0.8, 1.2, 1.6) and Mg1− x Ni x Co y Fe2− y O4 ( x, y = 0.0, 0.2, 0.4, 0.6, 0.8) have been fabricated using the microemulsion synthesis route. The synthesized materials are investigated for dc electrical resistivity measurements. The variation of dc electrical resistivity of these materials has been explainedon the basis of hopping mechanism of both holes and electrons.